Do drinking water plants retain microplastics? An exploratory study using Raman micro-spectroscopy - Luca Maurizi; Lucian Iordachescu; Inga V. Kirstein; Asbjørn H. Nielsen; Jes Vollertsen (Heliyon, 2023)
The retainment of microplastics (MPs) down to 1 μm by a Danish drinking water plant fed with groundwater was quantified using Raman micro-spectroscopy (μRaman). The inlet and outlet were sampled in parallel triplicates over five consecutive days of normal activity. For each triplicate, approximately 1 m3 of drinking water was filtered with a custom-made device employing 1 μm steel filters. The MP abundance was expressed as MP counts per liter (N/L) and MP mass per liter (pg/L), the latter being estimated from the morphological parameters provided by the μRaman analysis. Hence the treated water held on average 1.4 MP counts/L, corresponding to 4 pg/L. The raw water entering the sand filters held a higher MP abundance, and the overall efficiency of the treatment was 43.2% in terms of MP counts and 75.1% in terms of MP mass. The reason for the difference between count-based and mass-based efficiencies was that 1–5 μm MP were retained to a significantly lower degree than larger ones. Above 10 μm, 79.6% of all MPs were retained by the filters, while the efficiency was only 41.1% below 5 μm. The MP retainment was highly variable between measurements, showing an overall decreasing tendency over the investigated period. Therefore, the plastic elements of the plant (valves, sealing components, etc.) likely released small-sized MPs due to the mechanical stress experienced during the treatment. The sub-micron fraction (0.45–1 μm) of the samples was also qualitatively explored, showing that nanoplastics (NPs) were present and that at least part hereof could be detected by μRaman.